Field report PAC 671: Malaysian Communications and Multimedia Commission / Nurul Farhanah Shahrim - Shahrim, Nurul Farhanah (Universiti Teknologi MARA, Terengganu, 2024)
The regulatory agency in charge of the communications and multimedia sector in Malaysia is the Malaysian Communications and Multimedia Commission (MCMC). Its main function, as established by the Communications and Multimedia Act of 1998, is to promote and oversee the growth of the communications and multimedia industries. In addition to managing spectrum allotment, MCMC is responsible for maintaining fair competition, protecting consumer interests, encouraging universal access to communications services, and supporting the development of Malaysia's digital economy. In order to guarantee an evolving and competitive communications environment that benefits both industry participants as well as consumers equally, it plays a critical role in formulating policies, issuing licenses, and enforcing laws.